PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI KANTOR WALIKOTA TANGERANG SELATAN - Lestari, Nonda Ira; Boromeus, Supartomo Corolus (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of leadership and the physical work environment on employee performance in the south Tangerang mayor’s office, both sequentially and simultaneously the research approach used in this research is the quantitative method. The sampling technique used in this research used saturated sampling with a sample size of 52 respondents. Data analysis used validity test, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research are that leadership has a significant effect on employee performance with the regression equation Y = 12.573 + 0.652X1. hypothesis testing obtained a caltulated t value > t table or (7.206 > 1.676), thus, hol is rejected and hal is accepted, meaning that there is a significant equation Y = 7.310 + 0.811X2. hypothesis testing obtained a calculated t value > t table or (9.091 > 1.676). thus, Ho2 is rejected and Ha2 is accepted, meaning on employee performance. Leadership and physical work environment on employee performance. With the regression equation Y = (2.783 + 0.327X1 + 0.578) simultaneously significant leadership and physical work environment on employee performance.